Promoting intake of Cratylia argentea as a dry season supplement for cattle grazing Hyparrhenia rufa in the subhumid tropics - Ibrahim, M.; Franco, M.; Pezo, Danilo A.; Camero, A.; Araya, J.L. (Springer, 2001)
Cratylia argentea, a drought tolerant shrub, is known to produce significant amounts of fodder during the dry season but little is known of its nutritive value for feeding animals. Two studies of quality and intake of Cratylia argentea, as an arboreal protein supplement for crossbred dual purpose cattle grazing Hyparrenhia rufa in the dry season, were carried out in San Miguel de Barranca, Puntarenas, Costa Rica (January–May). The first experiment was a 2 × 2 factorial arrangement of two forms of C. argentea foliage presentation: 1) fresh or wilted; and 2) sprayed or not with sugarcane molasses diluted in water. Wilting did not affect crude protein content and in vitro dry matter digestibility (IVDMD) but treating fresh C. argentea with molasses increased IVDMD by from 55.6 to 60.8% (P < 0.01). Intake of fresh C. argentea increased by 32% with wilting and by 43% with molasses treatment. Pooling data across treatments, a quadratic relationship between dry matter intake of H. rufa (y) and the amount of N consumed in C. argentea (x) was found (y = 1.25 + 0.095x – 0.001x2). In the second experiment, milk production from the following treatments was evaluated: 1) chicken litter and molasses (D1); 2) chicken litter, sugar cane and wheat bran (D2); and 3) C. argentea, sugar cane and wheat bran (D3). Milk yields averaged 6.0 kg cow-1 day-1 and there were no significant differences between treatments. Milk fat was lower for D2 (2.7%), which had a higher amount of sugar cane in the diet, but differences were not significant. On the other hand, non-fat solids and lactose concentration of milk was higher (P < 0.05) for D2. Wilting or molasses treatment were effective management strategies for increasing dry matter intake of C. argentea. A higher dry matter intake of C. argentea was associated with increased intake of the fibrous H. rufa grass. Diets with C. argentea as the main protein source gave similar milk production levels and quality to those with chicken litter.